Assessment and optimization of energy smart window curtains - A pilot study to evaluate the energy performance and a parametric study to optimize the design of the newly developed Climate Curtains - Karim, Ali (My University, 2018)
According to the Swedish Energy Agency, buildings account for 40 % of Sweden’s demand for energy. Windows are often the weak spots of the building envelope concerning the energy performance, and for heated buildings, a tremendous amount of energy is lost through the windows. Lately, many new types of windows with improved thermal properties have been developed and have been used in new buildings. However, there are still a large number of old buildings all around the world and in Sweden, where windows with high U-value are used. Additionally, many buildings such as schools, offices and recreational homes are, on average, used actively for only a fraction of a year. Climate Curtain is a new energy smart window curtain, with the aim to reduce the heat losses through windows. By covering windows with Climate Curtain, for instance when the buildings are not occupied, the energy performance can be improved and become more economical and sustainable. The project aims to evaluate the energy performance of the curtains by in-situ measurements and simulations. In this project, 2 different designs of Climate Curtain have been studied. Curtain design (A) has the aim to increase the overall thermal resistance of window constructions and by that decrease the heat losses through windows. Curtain design (B) has an additional solar collector function which is aimed to capture some part of solar radiation striking the window and warm up the indoor temperature by small fans inside the curtain. The project investigates also the possibilities to optimize the design of the curtains regarding emissivity of the material and air velocity of the fans used in design (B). During the 27 days measurement campaign, interior and exterior temperatures, intensity of solar radiation and energy consumption in each test hut are continuously measured. The interior temperatures are kept constant using radiators. Results from the pilot study show that the total U-value of windows can be improved by using the curtains. For the case studied in this project, using the curtain design (A) improved the U-value of the window by approximately 50 %. For Curtain design (A) a surface to surface resistance of 0.65 m2·K W and for design (B) a resistance of 0.38 m2·K W is estimated. The solar collector function of design (B) has the ability to capture some part of solar radiation striking the window. It is also shown that the solar collector function is more profitable for windows with lower height. However, the efficiency of this function is always less than the case with just a window where solar radiation reaches the interior parts directly. The parameter study performed, shows a rather week relation between the efficiency of the solar collector function and the air velocity of the fans. Regarding the material used in the curtain, it is shown that the efficiency of the curtain can be further improved by using low emissivity material. Decreasing the emissivity of the material from 0.9 to 0.5 can theoretically improve the thermal properties of the curtain by almost 55 %. Based on the studies made in the project and the comparison between the 2 designs of the Climate Curtain, it is concluded that the optimal option is to have the curtain design (A) and pull the curtain up whenever the solar intensity increases above a certain value. It should also be mentioned that the results and conclusions of this report are very much case dependent and are based on the limited studies performed. In order to fully capture the properties and the long-term behaviour of the curtains, additional studies are required.
Keywords: Materialvetenskap; Byggnadsteknik; Materials Science; Building engineering